Kynurenines in the Pathogenesis of Peripheral Neuropathy During Leprosy and COVID-19 - Oliveira, Jéssica Araujo da Paixão de; Athaide, Mariana Martins de; Rahman, Atta Ur; de Mattos Barbosa, Mayara Garcia; Jardim, Marcia Maria; Moraes, Milton Ozório; Pinheiro, Roberta Olmo (Frontiers in Cellular and Infection Microbiology, 2022)
Inflammatory disorders are associated with the activation of tryptophan (TRYP) catabolism via the kynurenine pathway (KP). Several reports have demonstrated the role of KP in the immunopathophysiology of both leprosy and coronavirus disease 19 (COVID-19). The nervous system can be affected in infections caused by both Mycobacterium leprae and SARS-CoV-2, but the mechanisms involved in the peripheral neural damage induced by these infectious agents are not fully understood. In recent years KP has received greater attention due the importance of kynurenine metabolites in infectious diseases, immune dysfunction and nervous system disorders. In this review, we discuss how modulation of the KP may aid in controlling the damage to peripheral nerves and the effects of KP activation on neural damage during leprosy or COVID-19 individually and we speculate its role during co-infection.